HUBUNGAN USIA, PENGETAHUAN DAN DUKUNGAN SUAMI DENGAN TINGKAT KECEMASAN PADA IBU HAMIL DI TPMB SUNTER AGUNG - sindi fransiska; Fitrya Ayu Anggraini; Nina Sari (Politeknik Karya Husada, 2024)
Pregnancy is a natural process that causes physical and psychological changes in a mother due to hormonal changes in the body. Hormonal changes that occur during pregnancy often cause emotional changes and even anxiety. Data from the World Health Organization shows that in developing countries 10% of pregnant women experience mental disorders such as depression or anxiety, while in developing countries pregnant women have a high risk of experiencing psychological disorders at 15.6%. The aim of this study is to determine the relationship between age, level of knowledge and husband's support with the level of anxiety in facing childbirth in third trimester pregnant women at the Independent Midwife Practice Place in the Sunter Agung sub-district area. This study is a descriptive analytical study with a cross-sectional approach, with an incidental sampling technique, totaling 40 respondents from pregnant women in the third trimester. The data used in this study is primary data which was analyzed using the chi square test. There is a relationship between age (P-Value = 0.011, OR = 8.250, CI 95%), knowledge (P-Value = 0.000, OR = 22.500, CI 95%) and husband's support (P-Value = 0.000, OR = 17.067 CI 95%) with the level of anxiety in facing childbirth in third trimester pregnant women at the Independent Midwife Practice in the Sunter Agung sub-district area in 2024. It can be concluded that age, knowledge and husband's support are factors that are related to the level of anxiety in facing childbirth in third trimester pregnant women . With this, it is hoped that there will be education for pregnant women by involving the husband as the closest person, so that the husband can play a role during pregnancy, which can reduce anxiety in pregnant women. Keywords: Age, Knowledge, Husband Support, Anxiety